PENGARUH ATRIBUT PRODUK KOPI BUBUK INSTAN INDOCAFE TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN DI KOTA PONTIANAK - Arista, Dita; Dolorosa, Eva; Suharyani, Anita (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
This research aims to figure out the influence of the product attributes of Indocafe and the effect on customer satisfaction and loyalty in Pontianak city. The determination of the research location is determined intentionally (purposive method) in the city of Pontianak. The study used survey method with 150 respondents by using purposive sampling. Types of data used in this study are primary data and secondary data. Furthermore, the analysis is done by using structural equation modeling. The results showed that the variable of price, quality and packaging affect customer satisfaction. At the same time, quality has a significant effect to consumer loyalty. The most considerable influence on the quality variables and the overall contribution was the performance. Manufacturers need to improve the quality attributes, meaning the composition or content, the balanced flavor between sweet, sour and bitter, and the aftertaste that can last a long time so that consumers can have a good impression of Indocafe.